Activity of LY333328 in Experimental Meningitis Caused by a Streptococcus pneumoniae Strain Susceptible to Penicillin - Gerber, Joachim (American Society for Microbiology, 2001)
In a rabbit model of Streptococcus pneumoniae meningitis single doses of 10 and 2.5 mg of the glycopeptide LY333328 per kg of body weight reduced bacterial titers in cerebrospinal fluid (CSF) almost as rapidly as ceftriaxone at 10 mg/kg/h (changes in log CFU, −0.29 ± 0.21 and −0.26 ± 0.22 versus −0.34 ± 0.15/ml/h). A dose of 1 mg/kg was bacteriostatic (change in log CFU, 0.01 ± 0.11/ml/h). In two animals receiving LY333328 at a dose of 40 mg/kg the bacterial titers were reduced by 0.54 and 0.51 log CFU/ml/h. The penetration of CSF by LY333328 was 1 to 5%. The concentrations of lipoteichoic and teichoic acids in CSF and neuronal damage were similar in ceftriaxone- and LY333328-treated animals.